2020
DOI: 10.1111/mcn.12741
|View full text |Cite
|
Sign up to set email alerts
|

Improved sanitation is associated with reduced child stunting amongst Indonesian children under 3 years of age

Abstract: Growing evidence suggests that household sanitation is associated with child nutritional status in low‐ and middle‐income countries. This paper examined whether household access to improved sanitation facilities and sources of drinking water was associated with stunting and anaemia amongst children aged 6–35 months of age in Indonesia. The sample for the analysis comprised 1,450 children aged 6–35 months who participated in the end‐line survey of the maternal and young child nutrition security project in Asia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 23 publications
1
24
1
3
Order By: Relevance
“…On the other hand, a study done by Fink et al using the merged data set of 171 Demographic and Health Surveys found access to improved drinking water was associated with a lower risk of mild or severe stunting [ 55 ]. There is inconsistent findings of synergistic effects of improved drinking water and sanitation on childhood stunting [ 35 , 56 , 57 ]. The possible reasons for this variation may be related with initial water quality at the source, and with water handling practices during collection, transport and storage at the household level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study done by Fink et al using the merged data set of 171 Demographic and Health Surveys found access to improved drinking water was associated with a lower risk of mild or severe stunting [ 55 ]. There is inconsistent findings of synergistic effects of improved drinking water and sanitation on childhood stunting [ 35 , 56 , 57 ]. The possible reasons for this variation may be related with initial water quality at the source, and with water handling practices during collection, transport and storage at the household level.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, previous studies in Indonesia, on a smaller scale, found different information. Source of drinking water was not associated with stunting and anemia among children (Rah et al, 2020). Figure 3 is a scatter plot between the prevalence of stunted toddlers versus the percentage of households with access to proper sanitation in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…This tendency is in line with the results of previous studies which state that there is a relationship between latrine use and being stunted in children 7 . In previous studies, hygiene and sanitation have been shown to have a linear relationship with growth in children 15 . Poor sanitation increases the risk of infectious diseases and impaired absorption of nutrients.…”
Section: Table 3 Cross-tabulation Between Stunted Toddler Prevalencementioning
confidence: 87%